The biodiesel handbook - Knothe, Gerhard; Krahl, Jürgen, 1962-; Van Gerpen, Jon Harlan (AOCS Press, 2010)
"The second edition of this invaluable handbook covers converting vegetable oils, animal fats, and used oils into biodiesel fuel. The Biodiesel Handbook delivers solutions to issues associated with biodiesel feedstocks, production issues, quality control, viscosity, stability, applications, emissions, and other environmental impacts, as well as the status of the biodiesel industry worldwide."--Publisher's description.
Keywords: Biodiesel fuels.; elektronické knihy; electronic books